Success through failure? Four Centuries of Searching for Danish Coal - Kristin Ranestad; Paul Richard Sharp (European Historical Economics Society (EHES), 2020)
Natural resources, especially energy resources, are often considered vital to the process of economic development, with the availability of coal considered central for the nineteenth century. Clearly, however, although coal might have spurred economic development, development might also have spurred the discovery and use of coal. To shed light on this, we suggest that the case of resource poor Denmark, which spent centuries looking for coal, is illuminating. Specifically, we emphasize that the process of looking for coal and the creation of a natural resource industry in itself is important beyond the obvious dichotomy of haves and have-nots. We seek to understand this process and find that prices proved an important stimulus to coal surveys.
Keywords: N55; 330; Coal; Denmark; natural resources; mining